(untitled) - Eger, Ludvik (e-Pedagogium, 2001)
The article is focused on the role of the culture of school and it's development. By British authors is culture of organisatin part of TQM. There are presented results of our survey in this sphere.
Keywords: Rizeni kvality; kultura skoly; evaluace